Endogenous auxin and jasmonic acid levels are differentially modulated by abiotic stresses in rice - Du, Hao; Liu, Hongbo; Xiong, Lizhong (Frontiers in Plant Science, 2013)
Abiotic stresses such as drought, salinity, and adverse temperatures are major limiting factors for plant growth and reproduction. Plant responses to these stresses are coordinated by arrays of regulatory networks including the induction of endogenous abscisic acid (ABA), a well documented phytohormone for stress responses. However, whether or how these abiotic stresses affect the endogenous biosynthesis or metabolism of other phytohormones remains largely unknown. Here, we report the changes of endogenous indole-3-acetic acid (IAA) and jasmonic acid (JA) levels and expression of genes related to the biosynthesis or signalling of these hormones in rice under various abiotic stress conditions. The IAA content was decreased after drought stress, but it was significantly increased under cold and heat stresses. And the auxin-regulated gravitropism of root tip was inhibited by cold stress. Many genes involved in the IAA biosynthesis and signalling were changed in transcript level under these stresses, and the changes were essentially in agreement with the change of endogenous IAA level. Interestingly, the endogenous JA content was increased markedly under drought and cold stresses, but it was reduced by heat stress. Accordingly, many genes involved in JA biosynthesis and signalling were induced by drought and cold treatment but these genes were significantly suppressed by heat stress. We concluded that endogenous levels of IAA and JA were differentially regulated by abiotic stresses in rice, implying diverse roles of these hormones in stress responses.